ARTI SEBUAH NAMA (STUDI TENTANG PEMBERIAN NAMA DI MASYARAKAT BANYUMAS DAN KEBIJAKAN KEPENDUDUKAN) - Niken Paramarti Dasuki; Sendy Noviko; Sukarso Sukarso (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Giving a name at birth or birth name is often associated with various things, such as place, atmosphere, or event. The current era, where technological develops and increasing public access to the outside world through electronic equipment and everything based on the Internet is believed to have an influence on giving birth names to people. It is interesting to examine how parents currently consider giving names to their children; consider that naming is related to the population policy issued by the Indonesian Government, especially in the Population Identification Card (KTP) and Family Card (KK) services. This research located in Kotayasa and Karanggintung Villages, Sumbang District, Banyumas, aims to reveal and describe parents' considerations in giving names to their children and its relationship with population administration. This research uses a survey or questionnaire method targeting heads of families who have immature children (under 18 years). The sample used a proportional simple random sampling technique of 160 respondents. The interview method used to support the questionnaire method. Data analysis uses descriptive statistics. The results of this study show that around 60% of respondents said that considerations for giving names came from the media or television shows, both soap operas and other types, others from the Internet, and only around 15% looked for data about names and their meanings. Most of these names consist of two syllables. The myth about names as prayers only believed by around 50% of respondents.